Prognostic Value of Frontal QRS-T Angle in Patients without Clinical Evidence of Cardiovascular Disease (From the Multi-Ethnic Study of Atherosclerosis [MESA]) - Walsh, Joseph A (2013)
Abnormal frontal QRS-T angle on a 12 lead electrocardiogram (ECG) is associated with incident coronary heart disease and total mortality in a biracial cohort but there have been no studies to date examining QRS-T angle’s prognostic value across multiple ethnicities. We studied 6,814 participants (52.7% women, mean age 62) from MESA; a multi-ethnic cohort aged 45–84 free of clinical cardiovascular disease (CVD) at enrollment. Baseline examination included measurement of traditional risk factors and 12-lead ECG’s. Frontal QRS-T axis was defined as normal (<75(th) percentile), borderline (75–95(th) percentile) or abnormal (≥ 95(th) percentile) and participants were followed for the composite endpoint of incident CVD events: cardiovascular death, myocardial infarction, angina pectoris or heart failure. After 7.6 years of follow up there were 444 total events. Borderline ((HR 1.37 95% Confidence Interval (CI) (1.10,1.70)) and abnormal QRS-T angle (HR 2.2 95% CI (1.63, 2.97)) was associated with incident CVD events in multivariable-adjusted models. However, after adjusting for T wave abnormalities there was no statistically significant association of either borderline (HR 1.12 95% CI (0.90, 1.41)) or abnormal (HR 1.31 95% CI (0.93, 1.84)) QRS-T angle with incident CVD events. Abnormal frontal QRS-T angle predicts incident CVD events in a multiethnic population and this increased risk is primarily mediated through T wave abnormalities. QRS-T angle provides an easily interpretable, continuous marker of abnormal ventricular repolarization that can aid the everyday clinician in risk prediction.